2000
DOI: 10.1152/ajpheart.2000.279.6.h3040
|View full text |Cite
|
Sign up to set email alerts
|

Detection and sources of nonlinearity in the variability of cardiac R-R intervals and blood pressure in rats

Abstract: Beat-to-beat R-R interval (RRV) and systolic blood pressure (SPV) variability signals were obtained from unrestrained rats in baseline and under different pharmacological treatments. The origin and extent of the nonlinearity in both signals, as well as their degree of mutual coupling, was estimated using measurements from the correlation integral (CI) and recurrence quantification analysis (RQA). After the respiratory component of baseline signals was removed, the nonlinearity was lower in the RRV and disappea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 28 publications
7
34
1
Order By: Relevance
“…The significant decrease of ApEn, SampEn, and LZEn could be well explained by the terbutaline-induced decrease in the parasympathetic modulation of heart rate. It is well known that cardiac respiratory sinus arrhythmia is related to cardiac parasympathetic modulation, and sinus arrhythmia explains a major fraction of human heart rate variability at rest (8,18). SymDyn entropy, however, was surprisingly not decreased by terbutaline, whereas the another symbol dynamic measure, the percentage of forbidden words, was drastically increased by terbutaline.…”
Section: Discussionmentioning
confidence: 92%
“…The significant decrease of ApEn, SampEn, and LZEn could be well explained by the terbutaline-induced decrease in the parasympathetic modulation of heart rate. It is well known that cardiac respiratory sinus arrhythmia is related to cardiac parasympathetic modulation, and sinus arrhythmia explains a major fraction of human heart rate variability at rest (8,18). SymDyn entropy, however, was surprisingly not decreased by terbutaline, whereas the another symbol dynamic measure, the percentage of forbidden words, was drastically increased by terbutaline.…”
Section: Discussionmentioning
confidence: 92%
“…ANS activity in human and sheep fetuses (4) as well as in adult rats and humans (33) is variably dependent on behavioral states. In contrast to near-term ovine fetuses we studied and that are known to spend Ͼ90% of the time in REM or NREM sleep states (27), both adult rats and humans in the studies discussed above were awake (2,10). In adult sheep, rats, and humans, electrocortical activity changes similarly during low-voltage/REM and high-voltage/NREM sleep states (27).…”
Section: Discussionmentioning
confidence: 98%
“…Although respiratory activity in fetus near-term reflects maturation of central nervous system's (CNS) respiratory generators and exhibits fractal, i.e., nonlinear, properties (28), vagally mediated linear fHRV properties are not related to respiratory activity in sheep fetuses at the gestational age when we conducted our study (19), and the relation of vagally mediated nonlinear fHRV properties and fetal respiratory activity has not been studied. Unlike in antenatal life, studies on conscious adult rats suggest that vagal activity contributes to nonlinear HRV properties (2,10). In healthy adult awake humans, respiratory activity mediates the nonlinear HRV properties (25).…”
Section: Discussionmentioning
confidence: 99%
“…But what if, in fact, cardiac dynamics are actually non-linear? The truth is that it is now widely recognized that the functions and fluctuations of the heart are highly nonlinear [9]. Might it be concluded that as the sine wave is to the arterial pressure pulse, so are the mean and standard deviation to cardiac dynamics?…”
Section: The Rate Of the Heartmentioning
confidence: 99%